Analysis of Enthalpy Changes in Jackfruit Seed (Artocarpus heterophyllus L.) Fermentation Process Based on Yeast Mass - Dimas Ridho; Moondra Zubir; Ani Sutiani; Amanda Revalona Sitepu; Dita Indah Lorencia Silitonga; Maria Yovinta Silitonga; Muhammad Fisal (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This study investigates the fermentation process of jackfruit seeds (Artocarpus heterophyllus L.) as a bioethanol production source due to their high carbohydrate content. The research focuses on the effect of yeast mass on temperature fluctuations and reaction enthalpy (ΔH) during fermentation. Jackfruit seed flour was prepared and hydrolyzed with 5M HCl before fermentation with varying yeast masses. Temperature changes during fermentation ranged from 28.5°C to 32°C, depending on yeast mass, indicating the activity of Saccharomyces cerevisiae. The reaction enthalpy values for the samples were -126 J, -168 J, -504 J, and -1008 J, confirming the exothermic nature of the fermentation process